High-strength transparent antibacterial ultrathin paper and preparation method thereof

By using carboxy modified cellulose nanofibers and bialdehyde cellulose nanocrystals in ultrathin paper, combined with chitosan to prepare antibacterial composite coatings and undergo plasma treatment, the shortcomings of ultrathin paper in mechanical properties, antibacterial properties and transparency are solved, and ultrathin paper with high strength, good antibacterial properties and moderate transparency are achieved.

CN119663679AActive Publication Date: 2025-03-21SHANDONG CHENMING PAPER HLDG LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510198866.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-03-21
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

Existing ultra-thin papers have shortcomings in mechanical properties, antibacterial properties and transparency, and the addition of composite antibacterial ingredients will affect the transparency of the paper.

Method used

Antibacterial composite coatings are prepared by carboxy modified cellulose nanofibers and bialdehyde cellulose nanocrystals, combined with chitosan, and the hydrophilicity and antibacterial properties of the paper are improved through plasma treatment.

Benefits of technology

It improves the mechanical properties, antibacterial properties and transparency of ultra-thin paper, with an antibacterial rate of up to 99.9%, while maintaining the high strength and moderate transparency of the paper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides high-strength transparent antibacterial ultrathin paper and a preparation method thereof, and relates to the field of ultrathin paper. The preparation method of the high-strength transparent antibacterial ultrathin paper comprises the following steps: preparing carboxyl modified cellulose nanofibers, preparing dialdehyde cellulose nanocrystals, preparing an antibacterial composite coating, preparing raw paper of the ultrathin paper, and forming. According to the preparation method of the high-strength transparent antibacterial ultrathin paper, the transparency of the ultrathin paper can be further improved while the mechanical property and the antibacterial property of the ultrathin paper are improved; the prepared high-strength transparent antibacterial ultrathin paper has the characteristics of high strength, good flexibility and appropriate transparency, and the antibacterial rate can reach 99.9%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ultra-thin paper, and in particular to high-strength transparent antibacterial ultra-thin paper and a preparation method thereof. Background Art

[0002] Infections caused by Escherichia coli (Gram-negative bacteria) cause tens of thousands of illnesses each year, leading to a large number of hospitalizations and deaths each year. There are many solutions to treat these infections, but they all require high economic costs. Vaccination is one of the effective ways to solve these infections, but it also costs hundreds of billions of yuan each year, and its cost is also relatively high; and every year, tens of millions of children around the world cannot be vaccinated. In the prior art, there is also a more feasible epidemic prevention method, which is to prepare daily necessities with bactericidal functions, especially toilet paper and related paper-based products that people consume the most in daily life. Among them, toilet paper and table paper are essential items for people's daily life. According to statistics, the annual per capita consumption of toilet paper in my country exceeds 8.4kg. At the same time, as people pay more and more attention to healthy lifestyles, the toilet paper market is growing every year, but there are very few toilet paper products with bactericidal properties.

[0003] In our daily life, the safety and antibacterial properties of sanitary products are very important to our health, and the need to effectively control the spread of infectious diseases is becoming increasingly urgent. Among them, toilet paper and related paper-based products are the most used in people's daily lives. In order to minimize the use of paper products, the preparation of ultra-thin paper with high strength and good antibacterial properties has important technical significance and application value.

[0004] The prior art discloses ultra-thin paper prepared by using modified cellulose, which improves the mechanical strength of ultra-thin paper by adding modified cellulose into pulp and interacting with the surface groups of modified cellulose and raw materials. The cellulose-based ultra-thin paper prepared by this method shows unique properties and physical characteristics, such as transparency, density, mechanical strength, etc., and is expected to be used in the fields of medical treatment, hygiene, electronics, and intelligent packaging. However, the aforementioned cellulose paper-based materials still have many shortcomings, such as low mechanical properties and no functionality.

[0005] Chitosan is prepared by deacetylation of chitin from crustaceans such as shrimp shells and crab shells. It is a natural polysaccharide with abundant reserves and strong antibacterial properties. There are currently two antibacterial mechanisms. One is that chitosan molecules contain a large number of NH2-type active functional groups, which are protonated and positively charged, and can produce electrostatic effects with negatively charged anions such as sialic acid phospholipids on the bacterial cell wall, thereby restricting the free movement of microorganisms and hindering their reproduction; the other mechanism is that low molecular weight chitosan can invade bacterial cells, hinder the transcription of bacterial DNA to RNA, and block the growth and reproduction of bacteria. The prior art has disclosed the use of chitosan as an antibacterial agent in the preparation of paper-based materials, thereby giving the paper-based materials certain antibacterial functions. However, the antibacterial performance of paper-based materials using chitosan alone is still insufficient, and the addition of existing composite antibacterial components will have an adverse effect on the transparency of ultra-thin paper; at the same time, while improving the antibacterial performance and transparency of ultra-thin paper, the mechanical properties of ultra-thin paper also need to be further improved. Summary of the invention

[0006] In order to solve the technical problems existing in the prior art, the present invention provides a high-strength transparent antibacterial ultra-thin paper and a preparation method thereof, which can improve the mechanical properties and antibacterial properties of the ultra-thin paper while further improving the transparency of the ultra-thin paper.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing high-strength transparent antibacterial ultra-thin paper comprises the following steps: preparing carboxyl-modified cellulose nanofibers, preparing dialdehyde cellulose nanocrystals, preparing antibacterial composite coatings, preparing ultra-thin paper base paper, and forming; The method for preparing carboxyl-modified cellulose nanofibers comprises treating cellulose pulp with a citric acid-oxalic acid mixed organic acid solvent to prepare carboxyl-modified cellulose nanofibers; The method for preparing dialdehyde cellulose nanocrystals comprises: contacting sodium periodate with cellulose nanocrystals and then dialyzing to obtain dialdehyde cellulose nanocrystals; The method for preparing the antibacterial composite coating comprises: adding chitosan and dialdehyde cellulose nanocrystals into an acetic acid solution to prepare the antibacterial composite coating; The method for preparing the ultra-thin paper base paper comprises: mixing bleached kraft pine pulp, bleached kraft acacia pulp and carboxyl modified cellulose nanofibers to prepare the ultra-thin paper base paper; The molding method comprises the following steps: applying the antibacterial composite coating to the ultra-thin paper base paper, drying the base paper, and subjecting the base paper to plasma treatment to obtain the high-strength transparent antibacterial ultra-thin paper.

[0008] Preferably, in the preparation of the carboxyl-modified cellulose nanofibers, the citric acid content of the citric acid-oxalic acid mixed organic acid solvent is 25-50wt%, the oxalic acid content is 2-10wt%; more preferably, the citric acid content is 25-30wt%, the oxalic acid content is 2-4wt%, and the balance is water; Preferably, the treatment temperature of the citric acid-oxalic acid mixed organic acid solvent on the cellulose pulp is 110-130° C., and the treatment time is 1.5-3 h.

[0009] Preferably, in the preparation of carboxyl-modified cellulose nanofibers, the cellulose pulp is an absolute dry pulp of bleached kraft pine pulp, the ISO whiteness of the bleached kraft pine pulp is at least 86%, the fiber length is 2.25 mm, the fiber width is 28.0 μm, and the coarseness is 265 mg / km.

[0010] Preferably, in the preparation of dialdehyde cellulose nanocrystals, the contact reaction temperature of sodium periodate and cellulose nanocrystals is 25-60° C., and the contact reaction time is 2-4 hours; The molecular weight cut-off for dialysis is 12000-14000Da, and the dialysis time is 48-80h.

[0011] Preferably, in the preparation of dialdehyde cellulose nanocrystals, the amount of sodium periodate used is at least 1.1 times the weight of the cellulose nanocrystals; The average particle size of cellulose nanocrystals is 150 nm, the aldehyde content is 1.5 mmol / g, and the potential is -13 mV.

[0012] Preferably, in the preparation of the antibacterial composite coating, the concentration of chitosan in the antibacterial composite coating is 0.6-0.85wt%, and the concentration of dialdehyde cellulose nanocrystals is 0.15-0.4wt%.

[0013] Preferably, in the preparation of the ultra-thin paper base paper, the amount of bleached kraft pine pulp is 70-80 parts by weight; the amount of bleached kraft acacia pulp is 20-30 parts; and the amount of carboxyl-modified cellulose nanofiber is 0.1-1 part.

[0014] Preferably, the antibacterial composite coating is applied to the ultrathin paper and then dried, and the weight portion of chitosan in the antibacterial composite coating is 0.6-0.85 parts, and the weight portion of dialdehyde cellulose nanocrystals in the high-strength transparent antibacterial ultrathin paper is 0.15-0.4 parts.

[0015] Preferably, in the molding, the plasma atmosphere of the plasma treatment consists of helium and oxygen; The discharge power of the plasma treatment is 100-200W, the discharge frequency is 25-30kHz, the treatment time is 10-30min, and the treatment temperature is room temperature.

[0016] Furthermore, the method for preparing carboxyl-modified cellulose nanofibers comprises: treating cellulose slurry with a citric acid-oxalic acid mixed organic acid solvent, diluting with deionized water, and filtering to obtain a filter residue; washing the filter residue to neutrality, diluting with deionized water, and ultrasonically treating to obtain a carboxyl-modified cellulose nanofiber aqueous suspension; Preferably, the concentration of the carboxyl-modified cellulose nanofiber aqueous suspension is at least 0.8 wt %.

[0017] Preferably, the ultrasonic treatment power is 800-1000 W, and the ultrasonic treatment time is 20-40 min.

[0018] Furthermore, the method for preparing dialdehyde cellulose nanocrystals is to add sodium periodate to a cellulose nanocrystal aqueous solution for contact reaction, dilute with ethylene glycol, and dialyze to obtain dialdehyde cellulose nanocrystals.

[0019] Preferably, the concentration of the cellulose nanocrystal aqueous solution is at least 1 wt %.

[0020] Preferably, the mass volume ratio of sodium periodate to the cellulose nanocrystal aqueous solution is 1.3 g:100 mL.

[0021] Furthermore, in the preparation of the ultra-thin paper base paper, the bleached kraft pine pulp, the bleached kraft acacia pulp and the carboxyl-modified cellulose nanofiber aqueous suspension are uniformly mixed to prepare the ultra-thin paper base paper.

[0022] Preferably, in the preparation of the ultra-thin paper base paper, the ISO brightness of the bleached sulfate pine pulp is at least 86%, the fiber length is 2.25 mm, the fiber width is 28.0 μm, and the fiber thickness is 265 mg / km; the ISO brightness of the bleached sulfate acacia pulp is at least 85%, the fiber length is 1.1 mm, the fiber width is 16.5 μm, and the fiber thickness is 150 mg / km.

[0023] Furthermore, the forming method is that after the ultra-thin paper base paper is statically balanced, the antibacterial composite coating is applied to the ultra-thin paper base paper and then dried, and then plasma treated to obtain high-strength transparent antibacterial ultra-thin paper.

[0024] Preferably, the static equilibrium temperature is room temperature and the relative humidity is 60%.

[0025] A high-strength transparent antibacterial ultra-thin paper is prepared by the above-mentioned preparation method; the high-strength transparent antibacterial ultra-thin paper comprises the following components by weight: 70-80 parts of bleached sulfate pine pulp; 20-30 parts of bleached sulfate acacia pulp; 0.1-1 parts of carboxyl modified cellulose nanofibers; 0.6-0.85 parts of chitosan; and 0.15-0.4 parts of dialdehyde cellulose nanocrystals.

[0026] Compared with the prior art, the present invention has the following beneficial effects: 1) The method for preparing high-strength transparent antibacterial ultra-thin paper of the present invention comprises the following steps: preparing the high-strength transparent antibacterial ultra-thin paper by adopting all-natural polymer materials, adding carboxyl-modified cellulose nanofibers to the ultra-thin paper base paper during the preparation process to improve the strength; and treating the ultra-thin paper base paper with a natural composite antibacterial coating comprising chitosan and dialdehyde cellulose nanocrystals, wherein the dialdehyde cellulose has certain antibacterial properties, and after the dialdehyde cellulose nanocrystals are mixed in the coating, the synergistic effect of the two can be fully exerted, which can not only further enhance the antibacterial properties of the paper-based material, but also moderately offset the hydrophobicity of chitosan and maintain the fiber formation and water absorption. Furthermore, the inventors have found through research that the hydrophilicity of microorganisms and substrates is one of the key factors in enhancing the sensitivity of chitosan as an antimicrobial agent. The inventors have found through a large number of experimental studies that the coating formed by the composite antibacterial coating treated with oxygen plasma can effectively improve the hydrophilicity of ultra-thin paper; and spraying a composite antibacterial coating containing dialdehyde cellulose nanocrystals and chitosan on the surface of the ultra-thin paper base paper, combined with plasma treatment, can further significantly improve the antibacterial properties of the ultra-thin paper, and finally obtain ultra-thin paper with high strength, moderate transparency, and good antibacterial properties (can inhibit up to 99.9% of microbial growth).

[0027] 2) The preparation method of the high-strength transparent antibacterial ultra-thin paper of the present invention comprises adding carboxyl-modified nanocellulose into mixed pulp (bleached sulfate pine pulp, bleached sulfate acacia pulp), coating with a composite antibacterial coating, and cooperating with plasma treatment, which can improve the mechanical properties and antibacterial properties of the ultra-thin paper while further improving the transparency of the ultra-thin paper; the obtained high-strength transparent antibacterial ultra-thin paper has the characteristics of high strength, good flexibility, and appropriate transparency, and the antibacterial rate can reach 99.9%.

[0028] 3) The raw materials required for the preparation method of the high-strength transparent antibacterial ultra-thin paper of the present invention are all natural polysaccharide polymer materials, which are renewable resources; and the prepared high-strength transparent antibacterial ultra-thin paper is a completely biodegradable material, which is in line with the concept of carbon reduction development.

[0029] 4) The high-strength transparent antibacterial ultra-thin paper of the present invention has excellent antibacterial properties and has application prospects in the fields of biology, medicine, electronics and intelligent packaging. DETAILED DESCRIPTION

[0030] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0031] Example 1 The present embodiment provides a high-strength transparent antibacterial ultra-thin paper, which comprises the following components by weight: 75 parts of bleached sulfate pine pulp; 25 parts of bleached sulfate acacia pulp; 0.1 parts of carboxyl-modified cellulose nanofibers; 0.85 parts of chitosan; and 0.15 parts of dialdehyde cellulose nanocrystals.

[0032] This embodiment also provides a method for preparing high-strength transparent antibacterial ultra-thin paper, which is specifically: (1) Preparation of carboxyl-modified cellulose nanofibers The cellulose pulp is treated with a citric acid-oxalic acid mixed organic acid solvent. Specifically, 30g of citric acid, 3g of oxalic acid and 67g of deionized water are mixed, and stirred at 50°C for 30min to obtain a mixed organic acid solvent; then 10g of absolute dry cellulose pulp is added to 100mL of the above mixed organic acid solvent, and reacted in a polytetrafluoroethylene reactor at a temperature of 120°C and a speed of 500rpm for 2h, and the material after the reaction is added to 1000mL of deionized water, and stirred at a speed of 500rpm for 1h, and then vacuum filtered to obtain a filter residue, and the filter residue is washed with deionized water until the pH is neutral; the filter residue is diluted with deionized water to a concentration of 0.8wt%; then an ultrasonic emulsifier is used at a power of 900w for 30min to obtain a carboxyl-modified cellulose nanofiber (C-CNF) aqueous suspension, and the concentration of C-CNF in the C-CNF aqueous suspension is 0.8wt%.

[0033] The cellulose pulp is an absolute dry pulp of bleached kraft pine pulp, the ISO brightness of the bleached kraft pine pulp is 86%, the fiber length is 2.25 mm, the fiber width is 28.0 μm, and the coarseness is 265 mg / km.

[0034] (2) Preparation of dialdehyde cellulose nanocrystals In the dark, 1.3 g of sodium periodate was dissolved in 100 mL of cellulose nanocrystal aqueous solution (cellulose nanocrystal mass fraction was 1.0 wt%), the pH value of the system was adjusted to 3.0, and the reaction was carried out at 25 °C for 4 h. After the reaction, 200 mL of ethylene glycol was used to terminate the reaction, and then the obtained product was dialyzed with deionized water for 72 h (the molecular weight cutoff of the dialysis bag was 12000-14000 Da) to obtain dialdehyde cellulose nanocrystals.

[0035] Among them, in the cellulose nanocrystal aqueous solution, the average particle size of the cellulose nanocrystals is 150nm, the aldehyde content is 1.5mmol / g, and the potential is -13mV.

[0036] (3) Preparation of antibacterial composite coatings Chitosan was added to an acetic acid solution with a volume concentration of 1%, and stirred evenly to obtain a chitosan solution with a concentration of 0.85wt%; then the dialdehyde cellulose nanocrystals prepared above were added to the chitosan solution, and stirred and mixed for 30 minutes using a stirrer at a speed of 500rpm to obtain an antibacterial composite coating.

[0037] Among them, the chitosan is medium molecular weight chitosan, and the deacetylation degree is 97%.

[0038] In the antibacterial composite coating, the concentration of chitosan is 0.85wt%, and the concentration of dialdehyde cellulose nanocrystals is 0.15wt%.

[0039] (4) Preparation of ultra-thin paper base According to the weight of the above components, 75 parts of bleached kraft pine pulp, 25 parts of bleached kraft acacia pulp and a carboxyl modified cellulose nanofiber aqueous suspension (the content of carboxyl modified cellulose nanofiber in the aqueous suspension is 0.1 parts) were mixed evenly, and a paper with a basis weight of 15 g / m was prepared using a hand-made paper mold. 2 Ultra-thin paper base.

[0040] Among them, the ISO brightness of bleached sulfate pine pulp is 86%, the fiber length is 2.25mm, the fiber width is 28.0μm, and the coarseness is 265mg / km.

[0041] The ISO brightness of the bleached kraft acacia pulp is 85%, the fiber length is 1.1 mm, the fiber width is 16.5 μm, and the fiber thickness is 150 mg / km.

[0042] The total amount of the carboxyl-modified cellulose nanofiber aqueous suspension added is based on the carboxyl-modified cellulose nanofiber content in the carboxyl-modified cellulose nanofiber aqueous suspension being 0.1 parts (relative to other components of the aforementioned high-strength transparent antibacterial ultra-thin paper).

[0043] (5) Molding The ultra-thin paper base is placed in an environment with room temperature of 20°C and relative humidity of 60%, and is allowed to equilibrate for 12 hours; the antibacterial composite coating is then evenly coated on the ultra-thin paper base after equilibration, and then placed in a drying oven at 110°C for drying to obtain the coated ultra-thin paper base; a plasma system is then used to perform surface modification on the coated ultra-thin paper base to obtain a high-strength transparent antibacterial ultra-thin paper.

[0044] Among them, the coating amount of the antibacterial composite coating is 0.85 parts of chitosan in the antibacterial mixed coating (relative to other components of the aforementioned high-strength transparent antibacterial ultra-thin paper) and 0.15 parts of dialdehyde cellulose nanocrystals (relative to other components of the aforementioned high-strength transparent antibacterial ultra-thin paper).

[0045] During the surface modification treatment, the plasma atmosphere was composed of helium and oxygen, the volume ratio of helium to oxygen was 6:4, and the flow rate of the plasma atmosphere was 5 L / min; the discharge power of the plasma was 100 W, the discharge frequency was 25 kHz, the surface modification treatment time was 15 min, the surface modification treatment temperature was room temperature, and the plasma atmosphere pressure was maintained at 100 Pa.

[0046] Example 2 The preparation method of the high-strength transparent antibacterial ultra-thin paper of this embodiment adopts the technical scheme of Example 1, except that: in the step of preparing the ultra-thin paper base, the total amount of the carboxyl-modified cellulose nanofiber aqueous suspension added is added according to the carboxyl-modified cellulose nanofiber content in the carboxyl-modified cellulose nanofiber aqueous suspension being 0.25 parts (relative to the other components of the aforementioned high-strength transparent antibacterial ultra-thin paper).

[0047] Example 3 The preparation method of the high-strength transparent antibacterial ultra-thin paper of this embodiment adopts the technical scheme of Example 1, except that: in the step of preparing the ultra-thin paper base, the total amount of the carboxyl-modified cellulose nanofiber aqueous suspension added is added according to the carboxyl-modified cellulose nanofiber content in the carboxyl-modified cellulose nanofiber aqueous suspension being 0.5 parts (relative to other components of the aforementioned high-strength transparent antibacterial ultra-thin paper).

[0048] Example 4 The preparation method of the high-strength transparent antibacterial ultra-thin paper of this embodiment adopts the technical scheme of embodiment 1, and the difference is that: 1) in the step of preparing the ultra-thin paper base, the total amount of the carboxyl-modified cellulose nanofiber aqueous suspension is added according to the content of the carboxyl-modified cellulose nanofiber in the carboxyl-modified cellulose nanofiber aqueous suspension of 0.5 parts (relative to the other components of the aforementioned high-strength transparent antibacterial ultra-thin paper). 2) in the step of preparing the antibacterial composite coating, the concentration of chitosan is 0.75wt%, and the concentration of dialdehyde cellulose nanocrystals is 0.25wt%; and in the coating molding step, the coating amount of the antibacterial composite coating is coated according to the content of chitosan in the antibacterial mixed coating of 0.75 parts (relative to the other components of the aforementioned high-strength transparent antibacterial ultra-thin paper) and dialdehyde cellulose nanocrystals of 0.25 parts (relative to the other components of the aforementioned high-strength transparent antibacterial ultra-thin paper).

[0049] Example 5 The preparation method of the high-strength transparent antibacterial ultra-thin paper of this embodiment adopts the technical scheme of embodiment 1, and the difference is that: 1) in the step of preparing the ultra-thin paper base, the total amount of the carboxyl-modified cellulose nanofiber aqueous suspension is added according to the content of the carboxyl-modified cellulose nanofiber in the carboxyl-modified cellulose nanofiber aqueous suspension of 0.5 parts (relative to the other components of the aforementioned high-strength transparent antibacterial ultra-thin paper). 2) in the step of preparing the antibacterial composite coating, the concentration of chitosan is 0.65wt%, and the concentration of dialdehyde cellulose nanocrystals is 0.35wt%; and in the coating and molding step, the coating amount of the antibacterial composite coating is coated according to the content of chitosan in the antibacterial mixed coating of 0.65 parts (relative to the other components of the aforementioned high-strength transparent antibacterial ultra-thin paper) and dialdehyde cellulose nanocrystals of 0.35 parts (relative to the other components of the aforementioned high-strength transparent antibacterial ultra-thin paper).

[0050] Comparative Example 1 The method for preparing the ultra-thin paper of Comparative Example 1 adopts the technical solution of Example 3, except that: in the step of preparing the ultra-thin paper base, the addition of the carboxyl-modified cellulose nanofiber aqueous suspension is omitted.

[0051] Comparative Example 2 The preparation method of the ultrathin paper of Comparative Example 2 adopts the technical solution of Example 3, except that the step of preparing dialdehyde cellulose nanocrystals is omitted, and in the step of preparing the antibacterial composite coating, cellulose nanocrystals are used instead of dialdehyde cellulose nanocrystals.

[0052] Comparative Example 3 The preparation method of the ultra-thin paper of Comparative Example 3 adopts the technical solution of Example 3, except that: the surface modification treatment of the coated ultra-thin paper base paper by the plasma system is omitted in the coating and molding step.

[0053] Comparative Example 4 The preparation method of the ultra-thin paper of Comparative Example 4 adopts the technical solution of Example 3, except that: 1) in the step of preparing the ultra-thin paper base, the addition of the carboxyl-modified cellulose nanofiber aqueous suspension is omitted. 2) the preparation and use of dialdehyde cellulose nanocrystals and antibacterial composite coating are omitted, and the ultra-thin paper base is directly subjected to plasma surface modification treatment in the forming step.

[0054] The tensile index, E. coli antibacterial rate and transparency of the ultra-thin paper prepared in Examples 1-5 and Comparative Examples 1-4 were tested, and the specific technical means comparison and test results are shown in the following table:

[0055] From the data in the above table, it can be seen that the addition of carboxyl-modified fiber nanofibers in the pulp and the nano antibacterial composite coating significantly improve the antibacterial properties of the mixed pulp ultra-thin paper, and can also improve the tensile strength of the ultra-thin paper, without causing a significant adverse effect on the transparency of the ultra-thin paper. In addition, the ultra-thin paper with carboxyl-modified cellulose nanofibers added in the pulp has an advantage in improving the performance of all aspects compared to the ultra-thin paper without carboxyl-modified cellulose nanofibers added and only coated with antibacterial composite coating. And the plasma surface modification treatment of the coated ultra-thin paper base paper can further improve the antibacterial properties of the ultra-thin paper.

[0056] It can be seen from the above table that when carboxyl-modified cellulose nanofibers are added to the pulp and the content of dialdehyde cellulose nanocrystals in the antibacterial composite coating is 0.25-0.35wt%, the prepared high-strength transparent antibacterial ultra-thin paper has better mechanical properties and antibacterial properties, and the transparency of the ultra-thin paper does not change significantly.

[0057] Unless otherwise specified, all percentages used in the present invention are by mass.

[0058] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing high-strength transparent antibacterial ultra-thin paper, characterized in that: The method comprises the following steps: preparing carboxyl-modified cellulose nanofibers, preparing dialdehyde cellulose nanocrystals, preparing antibacterial composite coatings, preparing ultra-thin paper base paper, and forming; The method for preparing carboxyl-modified cellulose nanofibers comprises treating cellulose pulp with a citric acid-oxalic acid mixed organic acid solvent to prepare carboxyl-modified cellulose nanofibers; The method for preparing dialdehyde cellulose nanocrystals comprises: contacting sodium periodate with cellulose nanocrystals and then dialyzing to obtain dialdehyde cellulose nanocrystals; The method for preparing the antibacterial composite coating comprises: adding chitosan and dialdehyde cellulose nanocrystals into an acetic acid solution to prepare the antibacterial composite coating; The method for preparing the ultra-thin paper base paper comprises: mixing bleached kraft pine pulp, bleached kraft acacia pulp and carboxyl modified cellulose nanofibers to prepare the ultra-thin paper base paper; The molding method comprises the following steps: applying the antibacterial composite coating to the ultra-thin paper base paper, drying the base paper, and subjecting the base paper to plasma treatment to obtain the high-strength transparent antibacterial ultra-thin paper.

2. The method for preparing the high-strength transparent antibacterial ultra-thin paper according to claim 1, characterized in that: In the preparation of the carboxyl-modified cellulose nanofibers, the citric acid content of the citric acid-oxalic acid mixed organic acid solvent is 25-50wt%, the oxalic acid content is 2-10wt%, and the balance is water; The treatment temperature of the citric acid-oxalic acid mixed organic acid solvent for the cellulose pulp is 110-130° C., and the treatment time is 1.5-3 h.

3. The method for preparing the high-strength transparent antibacterial ultra-thin paper according to claim 1, characterized in that: In the preparation of carboxyl-modified cellulose nanofibers, the cellulose pulp is an absolute dry pulp of bleached kraft pine pulp, the bleached kraft pine pulp has an ISO whiteness of at least 86%, a fiber length of 2.25 mm, a fiber width of 28.0 μm, and a coarseness of 265 mg / km.

4. The method for preparing the high-strength transparent antibacterial ultra-thin paper according to claim 1, characterized in that: In the preparation of dialdehyde cellulose nanocrystals, the contact reaction temperature of sodium periodate and cellulose nanocrystals is 25-60° C., and the contact reaction time is 2-4 hours; The molecular weight cut-off for dialysis is 12000-14000Da, and the dialysis time is 48-80h.

5. The method for preparing the high-strength transparent antibacterial ultra-thin paper according to claim 1, characterized in that: In the preparation of dialdehyde cellulose nanocrystals, the amount of sodium periodate used is at least 1.1 times the weight of the cellulose nanocrystals; The average particle size of cellulose nanocrystals is 150 nm, the aldehyde content is 1.5 mmol / g, and the potential is -13 mV.

6. The method for preparing the high-strength transparent antibacterial ultra-thin paper according to claim 1, characterized in that: In the preparation of the antibacterial composite coating, the concentration of chitosan in the prepared antibacterial composite coating is 0.6-0.85wt%, and the concentration of dialdehyde cellulose nanocrystals is 0.15-0.4wt%.

7. The method for preparing the high-strength transparent antibacterial ultra-thin paper according to claim 1, characterized in that: In the preparation of the ultra-thin paper base paper, the amount of bleached kraft pine pulp is 70-80 parts by weight; the amount of bleached kraft acacia pulp is 20-30 parts by weight; The amount of carboxyl modified cellulose nanofibers used is 0.1-1 part.

8. The method for preparing the high-strength transparent antibacterial ultra-thin paper according to claim 7, characterized in that: In the molding, the antibacterial composite coating is applied to the ultra-thin paper base and then dried. The weight portion of chitosan in the antibacterial composite coating is 0.6-0.85 parts, and the weight portion of dialdehyde cellulose nanocrystals in the high-strength transparent antibacterial ultra-thin paper is 0.15-0.4 parts.

9. The method for preparing the high-strength transparent antibacterial ultra-thin paper according to claim 1, characterized in that: In the molding, the plasma atmosphere of the plasma treatment is composed of helium and oxygen; The discharge power of the plasma treatment is 100-200W, the discharge frequency is 25-30kHz, the treatment time is 10-30min, and the treatment temperature is room temperature.

10. A high-strength transparent antibacterial ultra-thin paper, characterized in that: The high-strength transparent antibacterial ultra-thin paper is prepared by the preparation method described in any one of claims 1 to 9; the high-strength transparent antibacterial ultra-thin paper comprises the following components by weight: 70-80 parts of bleached sulfate pine pulp; 20-30 parts of bleached sulfate acacia pulp; 0.1-1 parts of carboxyl-modified cellulose nanofibers; 0.6-0.85 parts of chitosan; and 0.15-0.4 parts of dialdehyde cellulose nanocrystals.

Citation Information

Patent Citations

  • Wallpaper with anti-bacterial function and preparation method thereof

    CN107142792A

  • Environment-friendly antibacterial wallpaper and preparation method thereof

    CN107268340A

  • Preparation method of bacteriostatic paper

    CN108560307A

  • Preparation method of plastic-free biomass-based oil-proof antibacterial food packaging paper

    CN110284368A

  • Preparation method and application of antibacterial nano-fiber

    CN110791829A